SAT0180 ANTIMALARIAL DRUGS ASSOCIATED RETINOPATHY IN SYSTEMIC LUPUS ERYTHEMATOSUS. (13th June 2020) - Larco Rojas, X. E.; Crespo Golmar, A.; Moriano, C.; López Robles, A.; Diez Alvarez, E.; Pérez Sandoval, T.
Abstract : Background: The antimalarials remain to be the main treatment for Systemic Lupus Erythematosus (SLE). Its most important limitation when you want to increase dose or remain using them is the occurrence of retinal toxicity, which appears in a small number of patients. Since the lesions can progress even with drug withdrawal is important to perform a screening for an early diagnosis. Objectives: To describe ocular toxicity in patients with SLE treated with antimalarials that attended the rheumatology office and to identify possible associated risk factors. Methods: We performed a cross-sectional, retrospective study of SLE patients diagnosed of antimalarial drugs associated retinopathy, that were included in the data base of the Rheumatology department in León`s Hospital between 2014-2019. Multiple clinical and therapeutic factors potentially associated with retinal toxicity were analyzed including: age, chronic kidney disease (CKD), liver failure, smoking, hypertension, Diabetes mellitus, presence of previous retinopathy, type of treatment, duration, daily dose and cumulative dose and tamoxifen intake. The diagnosis of retinopathy was performed by the Ophthalmology department. The dose of hydroxychloroquine (HCQ) used was of 400mg/day and chloroquine (CQ) 250mg/day. Results: 437 medical records were analyzed, 20 patients diagnosed of antimalarial retinopathy were included (4, 57%), 90% of them were women. The age of diagnosis was more than 40 years in 18 patients (90%) and more than 60 years in 10 (50%) with a median of 60 years (IQR: 32, 25). The duration of treatment was ≤ 5 years in 10 patients (50%), between 6-10 years in 6 (30%), between 11-15 years in 2(10%) and between 16-20 years in 2 (10%) with a median of exposure of 5, 5 years (IQR: 6, 5); 15 patients (75%) were in treatment with HCQ, with CQ 2 patients (10%) and with both of them sequentially 3 patients (15%). Of the group of patients treated with HCQ 35 % were above the global accumulated recommended dose (1000 g) and 71% of them were on treatment more than 10 years. In the group treated with CQ none were above the global recommended dose (460g). Of the 3 patients that took both drugs, two were above the recommended dose for HCQ. 25% of the patients had CKD and 10% liver failure, 20% of the patients were active smokers and 15% ex-smokers. 10% of the sample had previous retinopathy related with other comorbidities (age related retinopathy and diabetes), associating hypertension and diabetes mellitus in the same percentage (15%). Severe retinopathy was found in 1 patient (5%), mild-moderate in 9 patients (45%), retinopathy stages were not specified in 10 patients (50%). Conclusion: In our sample we observed a prevalence of antimalarials retinopathy of 4, 57%, similar of what is found in the literature. Half of the patients had retinopathy in a period of treatment ≤ 5 years, being a described risk factor the duration of treatment of more than 6 years. This early manifestation could be related to the presence of other comorbidities like hypertension, diabetes and CKD. Dose readjustment should be considered in patients with a period of treatment of more than 10 years. Age seems to be an associated factor for the development of antimalarials retinopathy and to perform a screening in the first year of treatment is important to rule out basal disease related with more risk to develop ocular toxicity. References: [1]Jorge, A., Ung, C., Young, L.H. et al. Hydroxychloroquine retinopathy — implications of research advances for rheumatology care. Nat Rev Rheumatol 14, 693–703 (2018). [2]Mukwikwi ER, Pineau CA, Vinet E. et al. Retinal Complications in Systemic Lupus Erythematosus Patients Treated with Antimalarial Drugs. J Rheumatol. 2019 Sep 1. jrheum.181102 [3]Abdulaziz N, Shah AR, McCune WJ. Hydroxychloroquine: balancing the need to maintain therapeutic levels with ocular safety: an update. Curr Opin Rheumatol. 2018 May;30(3):249-255. Disclosure of Interests: None declared